PENGARUH JARAK TANAM HEKSAGONAL TERHADAP PERTUMBUHAN DAN HASIL TIGA VARIETAS PADI - Muhammad Hatta (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2012)
ABSTRACT The objective of this study was to examine hexagonal plant spacing on growth and yield of three varieties of rice. In addition, this study was also aimed to examine interactions between the hexagonal plant spacing and the varieties on growth and yield of rice plants. The experiment applied a split plot design with four replications. Factors studied were (1) variety, placed as a main plot and (2) hexagonal plant spacing, placed as subplot. The results showed that effect of plant spacing on productive tiller number varied, depending on variety. In Pandan Wangi and Ciherang varieties, productive tiller numbers did not differ between plant spacing of 21 cm from a spacing of 25 cm. In contrast, in line Cot Irie, productive tiller of 25 cm plant spacing outnumbered that of plant spacing of 21 cm. Effect of plant spacing on panicle length was consistent on all varieties tested. Rice panicle length did not differ between plant spacing of 21 cm and 25 cm. Effect of plant spacing on potential yield per hectare was also consistent across all varieties tested. Plant spacing of 21 cm provided a potential yield per ha which was not significantly different from plant spacing of 25 cm. Line Cot Irie provided panicle length better than varieties Pandan Wangi and Ciherang. Line Cot Irie also provided the highest yield potential per hectare, while panicle length and potential yield per ha of Ciherang were not significantly different from Pandan Wangi.